Friction and Wear Characteristics of Indegenous ‘EPDM’ Rubber Under Dry Sliding Condition - Mukhopadhyay, Abhijit (Asian Review of Mechanical Engineering, 2014)
Ethylene Propylene Diene Monomer (EPDM) rubber emerges as a dominant elastomeric compound for major engineering applications like automobiles, constructions, electric and electronic industries and many more. The major engineering properties of EPDM are its outstanding heat, ozone and weather resistance ability. The resistance to polar substances and steam are also good. EPDM rubber has a common use as seals in automobiles. In the presentwork friction and sliding wear behaviors of indigenously developed ethylene propylene diene monomer rubber (EPDM) of different hardness have been studied against steel counterpart in dry condition. Different hardness of EPDM have been achieved by adding different proportion (parts per hundred) of carbon black (CB) with the main ingredients of EPDM. Tribo-testing has been carried out in a multi tribo tester TR-25 (Ducom, India). Experiments have been conducted at a constant load of 25N with different speeds and times. The frictional force, coefficient of friction (COF), mass loss and wear of EPDM rubbers have been determined from the test data and concluded accordingly. Present experimental work attempts to highlight some important tribo-characteristics of EPDM rubber as well as to shed light on various possible areas of further research works including the study of worn surface morphology using scanning electron microscope (SEM).